"Teacher...could you please allow us to play outside.." landscape design for children outdoor educational center - Shams Dolatabadi, Hosna Sadat; Ismail, Nor Atiah (Scottish Group, 2013)
Playing in the outdoor kindergarten environment provides unique opportunities for children in the critical period of early childhood. However; such experiences became less in compare to children‘s indoor educational activities, as the conventional ―equipment based‖ playground does not fulfill the requirements of being outdoors. At the same time, preschool children‘s participation in design is poorly noticed as they are considered inadequate to recognize their own needs. The research hypothesizes that an understanding of children‘s perception of their kindergarten play yard can ensure their emotional satisfaction and increases their physical behavior. This study investigated preschooler‘s preferred outdoor learning elements and activities in UPM kindergarten (FACE). This study adopted photo elicitation method including children and teachers interview. The findings suggested that children have shown their own desire towards outdoor activities and play elements. Majority of the children prefer free play in natural play environment that incorporated sustainable elements with natural composition. Natural play environment was found to able to help in increasing their desire for outdoor activities and at the same time, addressed the health and learning issues. Having more time spent with free creative and cognitive activities in natural play area will then, promote awareness of natural environment, better health and learning condition of the children.